The Cambridge handbook of communication disorders - Cummings, Louise (Cambridge : Cambridge University Press, 2014)
'Many children and adults experience impairment of their communication skills. These communication disorders impact adversely on all aspects of these individuals' lives. In thirty dedicated chapters, The Cambridge Handbook of Communication Disorders examines the full range of developmental and acquired communication disorders and provides the most up-to-date and comprehensive guide to the epidemiology, aetiology and clinical features of these disorders. The volume also examines how these disorders are assessed and treated by speech and language therapists and addresses recent theoretical developments in the field. The handbook goes beyond well-known communication disorders to include populations such as children with emotional disturbance, adults with non-Alzheimer dementias and people with personality disorders. Each chapter describes in accessible terms the most recent thinking and research in communication disorders. The volume is an ideal guide for academic researchers, graduate students and professionals in speech and language therapy'--
Part I. Developmental Communication Disorders: Cleft lip and palate and other craniofacial anomalies / John E. Riski -- Developmental dysarthria / Megan Hodge -- Developmental verbal dyspraxia / Brigid McNeill -- Developmental phonological disorder / Susan Rvachew -- Specific language impairment / Susan Ellis Weismer -- Developmental dyslexia / Catherine Christo -- Intellectual disability and communication / Katherine Short-Meyerson and Glenis Benson -- Emotional disturbance and communication / Gregory J. Benner and J. Ron Nelson -- Autistic spectrum disorders and communication / Courtenay Frazier Norburym -- Part II. Acquired Communication Disorders: Head and neck cancer and communication / Tim Bressmann -- Acquired dysarthria / Bruce E. Murdoch -- Apraxia of speech / Donald A. Robin and Sabina Flagmeier -- Aphasia / Roelien Bastiaanse and Ronald S. Prins -- Right hemisphere damage and communication / Yves Joanette, Perrine Ferre; and Maximiliano A. Wilson -- Dementia and communication / Jamie Reilly and Jinyi Hung -- Traumatic brain injury and communication / Leanne Togher -- Psychiatric disorders and communication / Karen Bryan -- Part III. Voice, Fluency and Hearing Disorders: Functional and organic voice disorders / Nadine P. Connor and Diane M. Bless -- Stuttering and cluttering / Kathleen Scaler Scott -- Hearing disorders / R. Steven Ackley -- Part IV. Management of Communication Disorders: Developmental motor speech disorders / Kirrie J. Ballard and Patricia McCabe -- Acquired motor speech disorders / Anja Lowitt -- Developmental language disorders / Laurence B. Leonard -- Acquired aphasia / Anne Whitworth, Janet Webster and Julie Morris -- Disorders of voice / Linda Rammage -- Disorders of fluency / J. Scott Yaruss -- Part V. Theoretical Developments in Communication Disorders: Motor speech disorders and models of speech production / Karen Croot -- Adult neurological disorders and semantic models / Tobias Bormann -- Language in genetic syndromes and cognitive modularity / Vesna Stojanovik -- Pragmatic disorders and theory of mind / Louise Cummings.
Includes bibliographical references and index.
Keywords: Communicative disorders -- Handbooks, manuals, etc